2018
DOI: 10.5564/pmas.v58i1.972
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal pollution of topsoil in settlement area, Darkhan city

Abstract: ХУРААНГУЙМонгол улсын томоохон хотуудын нэг болох Дархан хотын өнгөн хөрсний хортой хүнд металлууд (As, Co, Cr, Cu, Ni, Pb, V, Zn)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The exact location (longitudes and latitudes) of each sample point was determined using a global positioning system (GPS) instrument (Garmin Etrex 10 GPS, Garmin Ltd, Lenexa, Kansas, USA). Finally, the soil samples were transferred to the laboratory (Khanlab LLC, Ulaanbaatar, Mongolia) with the sample-box by cab for further analysis [23,24,25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact location (longitudes and latitudes) of each sample point was determined using a global positioning system (GPS) instrument (Garmin Etrex 10 GPS, Garmin Ltd, Lenexa, Kansas, USA). Finally, the soil samples were transferred to the laboratory (Khanlab LLC, Ulaanbaatar, Mongolia) with the sample-box by cab for further analysis [23,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…I geo was estimated using [27]:Igeo=log2(Cn1.5Bn) where C n is the concentration of an element in urban soil and B n is the background value. In this study, the chemical composition of non-effected soil at a site of each city [18,23,28] was chosen as the background values for calculating the I geo values. The constant 1.5 allowed us to analyze natural fluctuations in the concentration of a given substance in the environment and to detect very small anthropogenic influences [27].…”
Section: Methodsmentioning
confidence: 99%
“…This is particular an issue for those surfaces that are unstable due to a dipole moment normal to them in the bulk structure (Tasker's rule) [84] . Surfaces can stabilize themselves for example by surface reconstruction, formation of cation/anion vacancies or the adsorption of molecules from their surroundings [85,86] . So, it is not unlikely to expect a surface termination that has little to do with the bulk of the material.…”
Section: Introduction: Catalysis and Nanostructurementioning
confidence: 99%
“…Human-made pollution enters into soil, which aquatic ecosystems and increases the amount of PTEs in these environments, leading to many problems for animals and plants. 43,44 The average concentrations of arsenic, cadmium, chromium, copper, lead and zinc in the soils of Eghlid city in southern Iran were 45 Many studies have showed that the concentration of heavy metals in topsoil can vary. 10,11,16,26,45 This difference in concentration of heavy metals may be due to human activities such as industry, agriculture and urbanization.…”
Section: Resultsmentioning
confidence: 99%